Heterogeneity in Ewing sarcoma - Branford White, HA (2014)
Ewing sarcoma, an aggressive primary bone and soft tissue tumour is characterised by the expression of the chimeric transcription factor EWS-FLI1 in 90% of patients. This alters expression of many genes including activation of the Insulin Growth Factor (IGF) pathway via IGFBP3 supression. Phase I/II trials with an IGF-1 inhibitor have demonstrated tumour regression in a modest number of Ewing sarcoma patients. The aim of this thesis was to identify mechanisms contributing to the heterogeneity of resistance in Ewing sarcoma following inhibition with OSI-906, a dual kinase inhibitor of IGF-1 (IGF-1R) and Insulin (IR) receptors. The hypothesis was that mechanisms of resistance relate to heterogeneity of responses to signalling pathway activation and inhibition. Through selection, disruption of the pathway would identify subpopulations of cells both sensitive and resistant in their response allowing for interrogation of resistance mechanisms. A genome wide approach was taken to model the resistance profile of cell lines. Through developing a method of unbiased quantification, a panel of validated Ewing sarcoma cell lines (EuroBoNet) were imaged and segmented to assess the responses of biomarkers on signalling pathway activation. Heterogeneity was confirmed between cell lines. The application to diagnostic biopsies led to the identification of prognostic classifiers and cellular subpopulations with clinical prognostic significance. The distribution of Ki67 was found to be predictive of survival and cells with lower levels of CD99 in the cytoplasm were most discriminative. Parallel sequencing strategies (RNA-seq, whole exome sequencing, and aCGH/ SNP array) for genome-wide screening was carried out for point mutations, copy number changes and rearrangements. Systematic detection was used to characterise genomic rearrangements and functional validation performed. Resistant clones, formed via ENU mutagenesis of cell lines, were sequenced in order to demonstrate the resistance profile of OSI-906. In summary heterogeneity of Ewing sarcoma at the genomic and proteomic level can influence the signalling dependency of tumours and response to inhibitors. Genomic and proteomic profiling of tumour cells may be relevant to future developments of novel therapies.